Beyond PPE: a mixed qualitative–quantitative study capturing the wider issues affecting doctors’ well-being during the COVID-19 pandemic - Lyndsey Jayne Cubitt; Yu Ri Im; Ciaran James Scott; Louise Claire Jeynes; Paul David Molyneux (BMJ Open)
Objectives To understand the wider factors influencing and impacting upon hospital doctors’ well-being during the COVID-19 pandemic in England.Design Cross-sectional survey and mixed quantitative–qualitative analysis.Setting Acute National Health Service (NHS) Foundation Trust in England.Participants An online survey was circulated in early June 2020 to all 449 doctors employed by the Trust. 242 doctors completed the survey (54% response rate).Primary outcome measures Questions assessed occupational details, self-reported changes in physical and mental health, satisfaction with working hours and patterns, availability of personal protective equipment (PPE), medication and facilities, communication and sought to identify areas seen as having a significant effect on doctors’ well-being.Results 96% of respondents requiring PPE were able to access it. Nearly half of the respondents felt that their mental health had deteriorated since the start of the pandemic. Over a third stated that their physical health had also declined. Issues identified as having a negative impact on doctors included increased workload, redeployment, loss of autonomy, personal issues affecting family members, anxiety around recovery plans, inadequate access to changing and storage facilities and to rest areas that allow for social distancing. Doctors appreciated access to ‘calm rooms’ that were made available for staff, access to clinical psychology support, free drinks and free car parking on site.Conclusion The emerging themes are suggestive of increased burnout risk among doctors during the COVID-19 pandemic and encompass factors well beyond shortage of PPE. Small organisational initiatives and the implementation of changes suggested by survey respondents can have a positive impact on doctors’ well-being.